Factors Affecting Developer’s Decision on Green Residential Supply - Leong, Ruth; Ta Wee, Seow; Mohamed, Sulzakimin; Sarpin, Norliana (Research in Management of Technology and Business, 2021)
Malaysia population has gradually increase and housing demand has also been affected. In order to resolve and control the issues, government has taken proactive action with various incentives and support for construction industry and urged construction player to promote green concept in the past decades. However, bringing transition among housing industry from conventional concept to green concept is a huge challenge for developer. There are consists of various factors that influence developer decision in green residential supply. Therefore, the research question for this research paper will be focus on the factor influence developer’s decision in supplying green residential and strategic among developer’s decision in supplying green residential. The data collection stage was implemented qualitative method which through interview session and online method carry out with 12 developer companies in Johor Bahru. The result shows that cost factor is the factor influence developer’s decision in supplying green residential. The cost factor is due to high construction cost, maintenance cost, huge amount to engage Green Building Index (GBI) and building consultant fee. Hence, in term of strategic among developer’s decision in supplying green residential is also cost factor by focus on budget controlling, costing margin, cost efficiency and looking for reasonable resources. As conclusion, the research objectives are achieved and the research study has help to provide an actual overview for construction industry stakeholder and as well for researcher regarding the factor and strategic that influence developer’s decision in green residential supply.